2020
DOI: 10.1038/s41598-020-78347-6
|View full text |Cite
|
Sign up to set email alerts
|

Variation in selection constraints on teleost TLRs with emphasis on their repertoire in the Walking catfish, Clarias batrachus

Abstract: The high degree of conservation of toll-like receptors (TLRs), and yet their subtle variations for better adaptation of species in the host–pathogen arms race make them worthy candidates for understanding evolution. We have attempted to track the trend of TLR evolution in the most diverse vertebrate group—teleosts, where Clarias batrachus was given emphasis, considering its traits for terrestrial adaptation. Eleven C. batrachus TLRs (TLR1, 2, 3, 5, 7, 8 9, 13, 22, 25, 26) were identified in this study which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…TLR4, TLR5, TLR7, TLR13 genes are generally highly expressed in individuals with resistance to V. anguillarum infection. Diversity of TLR genes has also been reported in teleosts, comparative genomics studies have attributed this trend of divergence in teleost lineage to enhanced molecular evolutionary rates of nucleotide and protein coding sequences and higher rate of gain and loss of cis-regulatory elements that consequently alters morphology or function [ 50 , 51 ]. For the different antibacterial effects of TLR family members, the study of mice deficient in each TLR have demonstrated that each TLR has a distinct function in terms of PAMP recognition and immune responses [11] .…”
Section: Discussionmentioning
confidence: 99%
“…TLR4, TLR5, TLR7, TLR13 genes are generally highly expressed in individuals with resistance to V. anguillarum infection. Diversity of TLR genes has also been reported in teleosts, comparative genomics studies have attributed this trend of divergence in teleost lineage to enhanced molecular evolutionary rates of nucleotide and protein coding sequences and higher rate of gain and loss of cis-regulatory elements that consequently alters morphology or function [ 50 , 51 ]. For the different antibacterial effects of TLR family members, the study of mice deficient in each TLR have demonstrated that each TLR has a distinct function in terms of PAMP recognition and immune responses [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on fish TLRs have concentrated on identifying individual TLR members in diverse teleost fish species such as TLR7 and TLR8 in Barbel chub ( Squaliobarbus curriculus ) ( Jin et al, 2018 ), TLR21, TLR22, and TLR25 in Dabry’s sturgeon ( Acipenser dabryanus ) ( Qi et al, 2018 ), TLR1-TLR3, TLR5, TLR7-TLR9. TLR13, TLR22, TLR25, and TLR26 in Walking catfish ( Clarias batrachus ) ( Priyam et al, 2020 ). Furthermore, researchers have also examined what occurs when a pathogenic bacterium, virus, or ligand is used as a stimulator, with regard to expression profiles and signalling cascade genes ( Jiang et al, 2020 ; Muduli et al, 2021 ; Wang et al, 2021 ).…”
Section: Survey Methodologymentioning
confidence: 99%